Proceedings of International Conference on Making Sense of Converging Media 2013
DOI: 10.1145/2523429.2523447
|View full text |Cite
|
Sign up to set email alerts
|

How to Use 3D in Stereoscopic Mobile User Interfaces

Abstract: So far, little research has been devoted to the user centric design of mobile stereoscopic 3D user interfaces (UIs). In this paper, we focus on charting people's perceptions and suggestions on the purposes for which stereoscopic 3D (S3D) user interface designs could be used in typical mobile phone applications. For this, we conducted two user studies (n=33; n=27) charting initial user perceptions around four mobile S3D applications. The findings reveal that most commonly the stereoscopic effect was perceived t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…2 left) and which were shown to the user with an LG Optimus 3D P920 mobile phone. As a conclusion, the results showed that the stereoscopic effect was most often suggested to provide additional information about the item, to group the items, or to be used in holistic UI layout designs [30]. In Phase 2, several alternatives of the initial design were created, see Figure 2 (top right) for an example.…”
Section: Iterative Designmentioning
confidence: 96%
“…2 left) and which were shown to the user with an LG Optimus 3D P920 mobile phone. As a conclusion, the results showed that the stereoscopic effect was most often suggested to provide additional information about the item, to group the items, or to be used in holistic UI layout designs [30]. In Phase 2, several alternatives of the initial design were created, see Figure 2 (top right) for an example.…”
Section: Iterative Designmentioning
confidence: 96%
“…The question of how the stereoscopic depth effect could be used in UI design has been investigated in several studies. Using S3D is perceived as a potential way to group similar content items or to highlight contextual information in a user interface [53]. There have also been design proposals where object depth within S3D UIs has been considered as an informative parameter e.g.…”
Section: Hci Research In S3dmentioning
confidence: 99%
“…for grouping items or highlighting contextual information, has been suggested (Ventä-Olkkonen et al, 2013). However, this work has generally not considered the usability of such designs beyond the static laboratory environment (Please note, later referrals to S3D in this paper, if not specified in detail, refer to mobile S3D).…”
Section: Introductionmentioning
confidence: 99%